2009
DOI: 10.4049/jimmunol.0901841
|View full text |Cite
|
Sign up to set email alerts
|

Basophils Protect against Reinfection with Hookworms Independently of Mast Cells and Memory Th2 Cells

Abstract: Hookworms infect several hundred million people worldwide, causing malnutrition, anemia, and growth retardation. Infections generally result in a strong type 2 immune response, but the effector mechanisms that mediate worm expulsion remain poorly characterized. In this study, we determined the role of mast cells and basophils in protective immunity against the murine hookworm, Nippostrongylus Brasiliensis, during primary and secondary infection. Mast cell–deficient c-KitW-sh mice had lower serum IgE levels com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 38 publications
(46 reference statements)
3
84
0
1
Order By: Relevance
“…The source of IL-4 within IL-33KO mice was CD4 + T cells but also could include mast cells and basophils. Indeed, basophils are a major source of IL-4 during secondary immune responses, and were shown to promote secondary immunity against N. brasiliensis (26,(45)(46)(47). Thus, while multiple redundant mechanisms are functioning during secondary challenge infection, our data support a hypothesis that eosinophils serve a predominant role in worm destruction during anamnestic immunity against GI nematodes (48,49).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The source of IL-4 within IL-33KO mice was CD4 + T cells but also could include mast cells and basophils. Indeed, basophils are a major source of IL-4 during secondary immune responses, and were shown to promote secondary immunity against N. brasiliensis (26,(45)(46)(47). Thus, while multiple redundant mechanisms are functioning during secondary challenge infection, our data support a hypothesis that eosinophils serve a predominant role in worm destruction during anamnestic immunity against GI nematodes (48,49).…”
Section: Discussionsupporting
confidence: 73%
“…Considerable debate has centered upon the site of worm killing and the types of granulocytes required for immunity against rechallenge (26,27,39). Our data showed no differences in worm burdens between WT and IL-33KO mice at d 3 postsecondary challenge.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…IL-4, IL-5, and IL-13 were measured by standard ELISA. Serum IgE concentrations were determined as described (42). Serum IgG1 was determined using the SBA clonotyping system (Southern Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…By using depleting antibodies and constitutively basophildeficient Mcpt8Cre mice, we have shown previously that basophils contribute to protective immunity against Nb independently of mast cells and memory Th2 cells (13,42). Further, it was shown that basophils increase faster after secondary infection than after primary Nb infection, independently of IL-4 (43).…”
Section: Wt Mice Had No Competitive Advantage Over Fcrγmentioning
confidence: 99%